1973
DOI: 10.1203/00006450-197306000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Micropuncture Study of Albumin Transfer in Aminonucleoside Nephrosis in the Rat

Abstract: ExtractAlbumin concentration in the proximal tubules of normal rats and rats with aminonucleoside nephrosis (AMN) was estimated by means of a sensitive radioimmunoassay. Nephrotic animals were studied at the onset of proteinuria and when the nephrotic syndrome was fully established. Albumin concentration in the proximal tubule of normal male rats averaged 2.5 ± 0.3 mg/100 ml, whereas in early nephrotic rats it averaged 4.9 ± 1.3 mg/100 ml and in normal sized tubules of heavily proteinuric rats, 15.7 ± 3.3 mg/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 14 publications
(18 reference statements)
1
30
0
Order By: Relevance
“…4,5,7,23,51,52 Such concentrations are higher than those measured in the proximal tubular fluid of rats with experimental proteinuria using micropuncture studies in which the reported maximum albumin concentration was 7 g/L. 53 However, since the duration of protein exposure is much longer in in vivo settings, the total amount of proteins processed by proximal tubular cells in vivo far exceeds that of the cultured HK-2 cells. Therefore, 15 g/L of OA-Alb usedformostofourexperimentsisappropriateforin vitro protein-overload model.…”
Section: Cell Culturementioning
confidence: 75%
“…4,5,7,23,51,52 Such concentrations are higher than those measured in the proximal tubular fluid of rats with experimental proteinuria using micropuncture studies in which the reported maximum albumin concentration was 7 g/L. 53 However, since the duration of protein exposure is much longer in in vivo settings, the total amount of proteins processed by proximal tubular cells in vivo far exceeds that of the cultured HK-2 cells. Therefore, 15 g/L of OA-Alb usedformostofourexperimentsisappropriateforin vitro protein-overload model.…”
Section: Cell Culturementioning
confidence: 75%
“…For example, direct micropuncture experiments demonstrated that proximal tubular fluid albumin concentration of rats increased from 6 g/ml in the normal condition to 74 g/ml with immunologically induced nephrotic syndrome (39). In aminonucleoside nephrosis, the proximal tubule fluid albumin concentration ranged between 0.16 and 2.3 mg/ml (40). In the setting of a plasma cell dyscrasia, light chain production increases significantly, producing circulating concentrations of monoclonal light chain that can approach 100,000 mg/L (7,14).…”
Section: Discussionmentioning
confidence: 99%
“…Significant absorption and metabolism of protein occur along the proximal tubule, and the absorption rate varies according to the proximal tubular protein concentration (46). Micropuncture studies have demonstrated that single nephron albuminuria is increased after reduction of nephron number in rats with ADR nephrosis (37,47,53). Results (41 ).…”
Section: Histochemistrymentioning
confidence: 99%